2015
DOI: 10.1152/physiolgenomics.00057.2015
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq analysis of high NaCl-induced gene expression

Abstract: High extracellular NaCl is known to change expression of numerous genes, many of which are regulated by the osmoprotective transcription factor nuclear factor of activated T cells-5 (NFAT5). In the present study we employed RNA-Seq to provide a comprehensive, unbiased account of genes regulated by high NaCl in mouse embryonic fibroblast cells (MEFs). To identify genes regulated by NFAT5 we compared wild-type MEFs (WT-MEFs) to MEFs in which mutation of the NFAT5 gene inhibits its transcriptional activity (Null-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
4
28
0
Order By: Relevance
“…Besides Prss35, the expression of these factors was not detected in renal segments (1). However, these transcripts have been identified to be up‐regulated by hyperosmolality in MEFs (37). Publicly available databases indicated that these genes physiologically have a kidney‐specific expression pattern (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Besides Prss35, the expression of these factors was not detected in renal segments (1). However, these transcripts have been identified to be up‐regulated by hyperosmolality in MEFs (37). Publicly available databases indicated that these genes physiologically have a kidney‐specific expression pattern (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…For example, by RNA-Seq we recently identified hundreds of NFAT5 transcriptional targets in mouse embryo fibroblast cells (30). Transcriptional regulation by NFAT5 is the obvious explanation for the effect it might have on activity of any protein.…”
Section: Discussionmentioning
confidence: 99%
“…Other prominent genes are the ran-binding protein 3 like (RanBP3L) or the ring finger 183 (Rnf183). The expression of both genes is induced by hyperosmolality [15,38,39]. However, in Vhl-KO cells, the expression of both genes is significantly downregulated.…”
Section: Discussionmentioning
confidence: 97%
“…When we compare the changes in expression, we observed that Vhl-KO cells showed reduced expression of 33 unfavorable and induced expression of 22 favorable genes. But the upregulated expression of more unfavorable genes (56) and predominantly reduced expression of favorable genes (38) indicates that, in summary, the loss of functional Vhl in the mpkCCD cells induces an unfavorable gene expression pattern.…”
Section: Loss Of Vhl Function Leads To An Unfavorable Gene Expressionmentioning
confidence: 99%